2016
DOI: 10.3389/fpsyg.2016.00729
|View full text |Cite
|
Sign up to set email alerts
|

Metacognitions Are Associated with Subjective Memory Problems in Individuals on Sick Leave due to Chronic Fatigue

Abstract: Background: Subjective cognitive impairments are frequent, but poorly understood in patients with chronic fatigue. We hypothesized that maladaptive metacognitive beliefs at baseline were associated with baseline subjective cognitive impairments, that they predict subjective cognitive impairments at treatment termination, and that a reduction in maladaptive metacognitive beliefs was associated with less subjective cognitive impairments at treatment termination, independent of changes in fatigue, pain, insomnia,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…The lack of association may reflect that self-report questionnaires and neuropsychological tests relate to different concepts, tapping into different sources and facets of information (Williams et al, 2011). While self-report questionnaires may reflect metacognitive beliefs and metacognitive monitoring (Jacobsen et al, 2016), such subjective information typically lies beyond the scope of neuropsychological tests, such as the SST test.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of association may reflect that self-report questionnaires and neuropsychological tests relate to different concepts, tapping into different sources and facets of information (Williams et al, 2011). While self-report questionnaires may reflect metacognitive beliefs and metacognitive monitoring (Jacobsen et al, 2016), such subjective information typically lies beyond the scope of neuropsychological tests, such as the SST test.…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study reported for the first time the associations between dysfunctional metacognitive beliefs and subjective cognitive impairments in CFS patients (Jacobsen et al, 2016). Specifically, the baseline scores on the subscale of cognitive confidence were independently associated with the subjective cognitive impairment at the end of an occupational therapy-based intervention (Return-To-Work, RTW).…”
Section: Metacognition and Chronic Fatigue Syndrome (Cfs)mentioning
confidence: 98%
“…One study assessed the relationship between metacognitive beliefs and subjective memory impairments in a CFS sample (Jacobsen et al, 2016 ) and found total metacognitive beliefs were significantly associated with memory impairment.…”
Section: Resultsmentioning
confidence: 99%